The Mamluk Sultanate and the Mamluks seen by Ibn Taymiyya: between Praise and Criticism - Mehdi Berriah (Arabian Humanities)
Indubitably, Ibn Taymiyya is among those medieval Muslim theologians who have aroused the most interest in modern Western and Arab scholarship. This interest in Ibn Taymiyya has led to the production of a considerable number of academic works. While his fatwas and positions on dogmatic, legal, philosophical, and political questions are beginning to become well‑known, his position and vision concerning Mamluk power have been less frequently investigated. Paradoxically, close reading of the Mamluk sources shows that the authors of the period provided a fairly accurate account of the variable relations maintained by Ibn Taymiyya with certain great figures of the sultanate. However, his considerations of Mamluk power remain poorly understood. Based on an examination of the writings of Ibn Taymiyya and his contemporaries, this article attempts to shed light on the position of the famous Ḥanbalī theologian vis‑à‑vis the Mamluk Sultanate and the Mamluks in relation to religion and governance.